Application of Pluviothermic Quotient and Xerothermic-hygrothermic Indices to the Indian Sub-continent - Meher-homji, V. M. (Indian Forester, 1968)
Pluviothermic quotient of Emberger (1930, 1932) and xerothermic-hygrothermic indices of Bagnouls and Gaussen (1953, 1964) are calculated for 199 stations of the sub-continent to see their applicability to the vegetation types. The values of the quotient of the stations are plotted against the mean of the minima (temperature) of the coldest month (m). The stations group themselves fairly well according to their vegetation types. Temperate, subtropical (or tropical montane) and tropical types separate out vertically with the increasing value of m. The lower the values of the quotient, drier are the stations. Those having desert vegetation occupy the lowest position on the graph followed by increasingly wetter types: thorn forest, dry deciduous-, moist deciduous., semi-evergreen and wet evergreen forest A few stations are exceptional In that they do not fall in the expected area of the graph. Many of these are geographically situated at the boundary of two vegetation types. Transitional characters of the vegetation of these places may explain the anomalies. Xerothermic Index (X) Is a measure of the duration and intensity of the dry season in number of biologically dry days. Hygrothermic index (Y) Is a similar evaluation of the wet Season. When the values of X are plotted against those of Y, the temperature factor does not Intervene, yet the results are fairly satisfactory In distinguishing various vegetation types.